Efektivitas Model Pembelajaran Kooperatif Tipe Think Pair Share (TPS) Ditinjau Dari Sikap Sosial Siswa Kelas VI SDN Sekargadung 2 Kabupaten Mojokerto - Wandar Rizky Ramadhani; Conny Dian Sumadi (Pusat Riset dan Inovasi Nasional, 2023)
This study aims to (1) find out whether there is a significant influence of the TPS learning model in terms of the social attitude of cooperation and student confidence, (2) find out how the effectiveness of the TPS learning model is seen from the social attitude of cooperation and student confidence, (3) find out how learning is implemented TPS. This research is a quantitative research with experimental research type, the design used is Quasi Experimental Design with Pretest-Posttest Nonequivalent Control Group Design. ;Data was collected using a questionnaire, and observation. The results of the calculation of the Independent Sample t-test obtained t count = 6.378 and t table = 2.018 and obtained a significance value of 0.000. Based on the test criteria if t count > t table (6.378 > 2.018) and if the Sig. (2-tailed) < 0.05 (0.000 < 0.05) then Ho is rejected and Ha is accepted, while the Effect Size test obtains a large category with a value of 1.92, meaning that there is an effectiveness of the Think Pair Share (TPS) learning model in terms of social attitudes of cooperation and self-confidence of class VI students of SD Negeri Sekargadung 2, Mojokerto Regency.